Intraoperative, open-heart coronary angiography in severe acute aortic valve endocarditis. (31st December 2018) - van der Linden, Marcel; Heuts, Samuel; Veenstra, Leo; Lorusso, Roberto
Abstract: We present the use of intraoperative open-heart coronary angiography in a patient with aortic valve endocarditis and extensive coronary calcification on coronary computed tomography angiography. Open-heart angiography was performed intraoperatively and revealed no significant stenoses. Aortic valve replacement without concomitant bypass surgery was performed, and the patient had an uneventful postoperative course.